A PROPÓSITO DO ANTI-SEMITISMO - Póvoa, Carlos Alberto (Caminhos de Geografia, 2001)
The text looks for to show that the " Aryan " individual doesn't exist and yes a systematic prejudice against the Jews. They created an identity to strengthen the anti-Semitism. European intellectuals involved in the constants explanations on the arianismo, they try without success to explain the raíz of this superior race the one of the Jews.